Development and usability evaluation of an educational game for learning data structure concepts involving sorting, queue, and stack - Endito Harisnanto; Sukirman Sukirman (Cendikia : Media Jurnal Ilmiah Pendidikan, 2026)
Learning data structure concepts at the Junior High School (SMP) level is often hampered by conventional delivery methods. Minimal visual representation sometimes makes it difficult for students to imagine how data is structured and processed, which impacts their lack of understanding and computational thinking skills. This study aims to develop and evaluate an HTML5-based educational game called "DATA WORLD" designed to help 8th-grade junior high school students understand the concepts of Array, Stack, and Queue data structures. This study uses the Research and Development (R&D) method with the ADDIE model consisting of five stages: Analysis, Design, Development, Implementation, and Evaluation. The game was developed using Construct 3 software and its effectiveness was evaluated on 32 8th-grade junior high school students using the System Usability Scale (SUS) instrument. The development results show that this game functionally succeeds in visualizing how data structures work concretely through document sorting challenges for sorting, First-In-First-Out (FIFO) customer queue simulations for queues, and Last-In-First-Out (LIFO) block stacking activities for stacks. Usability testing yielded an average SUS score of 82.5%, indicating excellent user acceptance. In conclusion, this educational game has proven functionally and pedagogically feasible as a companion learning tool for data structures. The interactive approach effectively bridges gaps in student understanding through a visual learning experience that is self-paced, enjoyable, and aligned with the learning outcomes of the informatics curriculum. Eighty-one percent of participants had never played a similar educational game before, ensuring authentic and unbiased assessments.